The complete mitochondrial genome of Chinese minnow (Rhynchocypris oxycephalus) and its phylogenetic analyses. Issue 8 (3rd August 2021) - Zhang, Cheng; Zhang, Shun; Tian, Zhe; Cheng, Shun; Wang, Danli; Xu, Shanliang
Abstract: The complete mitochondrial genome can provide novel insights into understanding the mechanism underlying mitogenome evolution. In the present study, the whole mitochondrial genome of Rhynchocypris oxycephalus was determined to 16608 bp (GenBank accession No: MW057563), including 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and one control region. The overall base composition was 28.62% A, 27.23% T, 26.31% C and 17.84% G, with a total A + T content of 55.85%. The Maximum Likelihood tree showed that the phylogenetic relationship is closer between R. oxycephalus and Phoxinus oxycephalus jouyi than the other species. The whole mitogenome of this species will be useful for the future animal evolutionary, phylogenetic relationship, and genomic studies in the genus Phoxinus .